unOrdinary. Volume 2 - uru-chan (Comics writer and artist) (HarperAlley, an imprint of HarperCollins Publishers, 2024)
"Ever since Wellston High's ace, Seraphina, was suspended, the hierarchy of the school has been unstable. Not only are the high-tiers on edge, but the carefully crafted persona John has built to survive his bullying is crumbling, and Arlo is beginning to suspect that John may be a real threat to the social order. But when a new danger from the outside world hits too close to home, everyone has to put their differences aside to save one of their own and uncover a conspiracy that threatens them all."--Back cover.